A Blueprint for Transitioning Pharmacy Residents Into Successful Clinical Faculty Members in Colleges and Schools of Pharmacy - Wanat, Matthew A. (American Journal of Pharmaceutical Education, 2013)
With the increase of new pharmacy colleges and schools throughout the country, the number of open clinical academic pharmacy positions continues to grow. Considering the abundance of clinical faculty positions available nationwide and the increased likelihood of current pharmacy residents transitioning from residency directly into academia, pharmacy residents must be prepared to succeed in the role of new clinical faculty member. However, no blueprint or recommendations have yet been provided to facilitate this transition. The purpose of this review article is to evaluate the literature regarding transitioning pharmacy students and/or residents into faculty roles. The literature reviewed represents nursing, medical, graduate school, and engineering disciplines because no literature on this topic was available from the pharmacy profession. Based on the recommendations provided in the literature and on the authors’ experience at their college, they created a blueprint consisting of 7 components to help residents transition directly into their roles as faculty members.